1998
DOI: 10.1088/0029-5515/38/4/312
|View full text |Cite
|
Sign up to set email alerts
|

Plasma behaviour with molecular beam injection in the HL-1M tokamak

Abstract: A new method of gas fuelling has been introduced in the HL-1M tokamak. The method consists of a pulsed high speed molecular beam formed by a Laval type nozzle. The velocity of the well collimated hydrogen beam is about 500 m/s. About 6 × 10 19 molecules pass through the nozzle and into the vacuum chamber in each pulse. A series of helium pulses was injected into the HL-1M low density (ne = 4 × 10 18 m −3 ) hydrogen plasma. With penetration depth up to 12 cm, the ramp-up rate of the electron density, dne/dt, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 9 publications
0
39
0
1
Order By: Relevance
“…SMBI has been implemented on the HL-1M tokamak [471,472], the HT-7 tokamak [473] and the W7-AS stellarator [474]. A Laval nozzle is utilized to inject a well collimated supersonic jet in the plasma (typically 5 10 19 particles per pulse with an injection time ranging from tens to hundreds of ms [471]). Gas speeds higher than 1 km/s have been obtained [475], to be compared with 300 m/s typical of gas puffing.…”
Section: Supersonic Gas Jet and Low Field Side Puffingmentioning
confidence: 99%
“…SMBI has been implemented on the HL-1M tokamak [471,472], the HT-7 tokamak [473] and the W7-AS stellarator [474]. A Laval nozzle is utilized to inject a well collimated supersonic jet in the plasma (typically 5 10 19 particles per pulse with an injection time ranging from tens to hundreds of ms [471]). Gas speeds higher than 1 km/s have been obtained [475], to be compared with 300 m/s typical of gas puffing.…”
Section: Supersonic Gas Jet and Low Field Side Puffingmentioning
confidence: 99%
“…Therefore, it is very important to use deep and local particle perturbation source for the particle transport study in the core plasma. On HL-1M tokamak, experiments have confirmed that the supersonic molecular beam injection ͑SMBI͒ can penetrate more deeply and locally than general gas puffing, 13,14 thus the SMBI could be a good and controllable perturbation source for particle transport study. In HL-2A, the local density profile is measured by an O-mode broadband microwave reflectometry, 15 whose microwave frequency is K a band ͑26.5-40 GHz͒ and U band ͑40-60 GHz͒, and which covers a density range from 0.8 to a͒ Electronic mail: xiaoww@swip.ac.cn.…”
Section: Introductionmentioning
confidence: 99%
“…To study the transport features of the pITB, the density modulation generated by SMBI has been used [7]. Fig.…”
Section: Spontaneous Internal Particle Transport Barriermentioning
confidence: 99%